An imbalancing act: the delayed dynamic response of the Kaskawulsh Glacier to sustained mass loss. Issue 262 (29th April 2021) - Young, Erik M.; Flowers, Gwenn E.; Berthier, Etienne; Latto, Rebecca
Abstract: The Kaskawulsh Glacier is an iconic outlet draining the icefields of the St. Elias Mountains in Yukon, Canada. We determine and attempt to interpret its catchment-wide mass budget since 2007. Using SPOT5/6/7 data we estimate a 2007–18 geodetic balance of −0.46 ± 0.17 m w.e. a −1 . We then compute balance fluxes and observed ice fluxes at nine flux gates to examine the discrepancy between the climatic mass balance and internal mass redistribution by glacier flow. Balance fluxes are computed using a fully distributed mass-balance model driven by downscaled and bias-corrected climate-reanalysis data. Observed fluxes are calculated using NASA ITS_LIVE surface velocities and glacier cross-sectional areas derived from ice-penetrating radar data. We find the glacier is still in the early stages of dynamic adjustment to its mass imbalance. We estimate a committed terminus retreat of ~23 km under the 2007–18 climate and a lower bound of 46 km 3 of committed ice loss, equivalent to ~15% of the total glacier volume.